Influence of Chemical Permeation Enhancers on the in vitro Skin Permeation of Minoxidil through Excised Rat Skin: A Mechanistic Study: Influence of Chemical Permeation Enhancers on the in vitro Skin Permeation of Minoxidil - Eskandar Moghimipour,; Anayatollah Salimi,; Ali Talebpour Jahromi, (Iranian Journal of Pharmaceutical Sciences, 2018)
Minoxidil, a pyrimidine derivative (2, 4-diamino-6-piperidinopyrimidine-3-oxide) is the only topical medical treatment with proven efficacy for the treatment of androgenic alopecia that showed low skin penetration and bioavailability. The main aim of this research was to investigate the effect of some permeation enhancers on the in vitro skin permeability of minoxidil. Minoxidil permeability experiments through rat skin pretreated with some of permeation enhancers namely, Urea, Eucalyptus oil and Menthol were performed in fabricated Franz diffusion cells and compared with hydrated rat skin as control. The permeability parameters evaluated include steady-state flux (Jss), permeability coefficient (Kp), and diffusion coefficient (D). The penetration enhancer’s permeability enhancement mechanisms were investigated by comparing of changes in peak position and their intensities of asymmetric (Asy) and symmetric (Sym) C-H stretching, C=O stretching, C=O stretching (Amide I) and C-N stretching of keratin (Amide II) absorbance using Fourier transform infrared spectroscopy (FTIR), as well as by comparing mean transition temperature (Tm) and their enthalpies (ΔH) using differential scanning calorimetry (DSC). Minoxidil permeability parameters through rat skin, were evaluated with and without chemical enhancers such as Eucalyptus oil, menthol, and urea. The skin showed barrier for minoxidil permeability through whole skin and that diffusion into the skin was the rate-limiting step for drug flux. Urea, Eucalyptus oil, and Menthol were the most effective enhancers as they increased flux 1.86, 2.16, and 1.75 times and diffusion coefficient 3.25, 1.34 and 2.16 folds in comparison with hydrated skin, respectively. FTIR and DSC results showed lipid fluidization, extraction, disruption of lipid structure and irreversible denaturation of proteins in the SC layer of skin by permeation enhancers.